Impact of epidermal growth factor and/or β-mercaptoethanol supplementations on the in vitro produced buffaloes' embryos - Ahmed, Ahmed Ezzat; Sindi, Ramya Ahmad; Yousef, Nasra Ahmed; Hussein, Hassan A.; Badr, Magdy R.; Syaad, Khalid M. Al; Al-Saeed, Fatimah A.; Hassaneen, Ahmed Saad A.; Abdelrahman, Mohamed; Ali, Montaser Elsayed (Frontiers in Veterinary Science, 2023)
The present study investigated the effects of epidermal growth factors (EGF) and/or β-Mercaptoethanol (βME) supplementations to oocyte maturation, fertilization, and culture media on the buffalo in vitro embryo production. The ovaries were collected and transferred within 2 hours to the laboratory. The cumulus oocytes complexes were aspirated from 3-8 mm diameter follicles. Firstly, EGF; 0, 10, 20, or 50 ng/mL or βME; 0, 25, 50, 100, or 200 μM were supplemented to the in vitro maturation (TCM-199), fertilization (IVF-TALP), or culture (IVC: SOF) media. Our results revealed that supplementing EGF (20 ng/mL) to the TCM-199, IVF-TALP, or SOF media could efficiently improve the growth rates and development of buffalos' embryos, while EGF (50 ng/mL) could stimulate the embryo production only after treatment of the IVF-TALP /or SOF media, but not the IVM medium. However, βME was less efficient than EGF; it stimulated the growth rates of buffalo embryos when supplemented with the maturation and fertilization (IVF-TALP) media in a 50 μM concentration. Secondly, combined EGF (20 ng/mL) and βME (50 μM) were supplemented to the maturation media as effective concertation. The combined treatment of EGF (20 ng/mL) and βME (50 μM) showed no significant enhancing effect on the buffalo embryos compared to each alone. For future perspectives, further study is required to examine the effects of combined EGF and βME on the maturation and fertilization of buffalo oocytes at different categories of age and seasonal localities.